In Conversation with Yara Sharif. - Musmar, Aya; Sharif, Yara (Journal of Architectural Education)
Yara Sharif is a Senior Lecturer and a practitioner with an interest in design as a means to facilitate and empower "forgotten" communities, while also interrogating the relationship between politics and architecture. Combining research with design, her work runs parallel between the architecture practice Golzari-NG Architects and the school of architecture at the University of Westminster. Sharif co-founded Palestine Regeneration Team (PART), which is a design-led research group that aims—through speculative and live projects—to search for creative and responsive spatial possibilities to heal the fractured landscape. Sharif's work has won a number of awards including the RIBA's President's Award for Research 2016 on "Cities and communities" category. Sharif has also contributed to several collaborative projects with Palestinian NGO Riwaq which won the Holcim Commendation Award for Sustainable Construction in the MENA Region 2014—Beit Iksa Eco Kitchen, and The Aga Khan Award for Architecture 2013 for the Regeneration of Birzeit Historic Centre.